Antimicrobial Efficacy of Successive Seed Extracts of Tephrosia purpurea - Thetwar, L.K.; Shrivastava, Alka; Shrivastava, Seema; Deshmukh, N.C.; Augor, M.R.; Tandon, R.C. (Asian Journal of Chemistry, 2010)
The seed extracts of the plant Tephrosia purpurea were tested for their antimicrobial and antifungal properties in various solvents against some human, animal and plant pathogenic bacteria. The study depicted that the seed extract showed a good inhibition effect against all the tested microorganisms.